Optimalisasi Penerapan Sistem Rainwater Harvesting (RWH) di Lingkungan Politeknik Negeri Bandung dalam Rangka Konservasi Sumber Daya Air - Karnisah, Iin; Enung, Enung; Widyantoro, Frenki Tres; Fadli, Dicky Muhamad; Sari, Risna Rismiana; Kusuma, Yusmiati; Juarti, Ery Radya; Noorlaelasari, Yullianty; Muchtar, Muchtar (Jurnal Komposit: Jurnal Ilmu-ilmu Teknik Sipil, 2026)
This study aims to optimize the Rainwater Harvesting (RWH) system at Bandung State Polytechnic as a strategy for water resource conservation and strengthening the Green Campus concept. The research was conducted by identifying the existing condition of the RWH system at 25 campus building points, analyzing hydrological potential using BMKG rainfall data from 2014–2024, as well as evaluating efficiency and developing technical optimization recommendations. The existing RWH system is dominated by tanks with a capacity of 1,050–2,000 liters, which do not yet function optimally due to limited capacity, channel blockages, and variations in pipe diameter. The analysis shows an average annual rainfall of 2,831 mm with a potential rainwater catchment of up to 70 m³ per month, sufficient to meet 25–30% of the campus's non-potable water demand. System optimization is proposed by increasing tank capacity to 5,000–10,000 liters, using 3–4 inch pipes, and implementing multi-layer filtration and automated control, thus increasing system efficiency to 40–60%. The integrated system prototype in classrooms and laboratories has been proven to reduce PDAM water consumption by 40% and surface runoff by up to 35%. The research outcomes support the achievement of UI GreenMetric water conservation indicators and contribute to the realization of Sustainable Development Goals (SDGs) points 6 and 13. This study provides recommendations for an adaptive RWH system replication model for other educational institutions in Indonesia to manage water resources sustainably and efficiently.​